Helium plasma dermal resurfacing: VISIA CR assessment of facial spots, pores, and wrinkles—Preliminary findings - Holcomb, John David (Journal of cosmetic dermatology, 2021)
Objectives Effects of low energy, single‐pass helium plasma dermal resurfacing (PDR) treatment on brown spots, enlarged pores, and wrinkles—preliminary findings. Methods Twenty two subjects (64.6 ± 6.6 years) with Fitzpatrick Wrinkle and Elastosis Scale score (FWS) of ≤2 and seeking improvement of facial appearance were included in this subanalysis. All subjects received a single, one‐pass, full face, and low power helium PDR treatment. Standard digital images were collected using the VISIA‐CR (Canfield Scientific Inc.) at baseline and 3 months after treatment with images assessed for improvement in FWS and for improvements in brown spots, enlarged pores, and wrinkles by proprietary automated image processing algorithms. Results Nearly all subjects demonstrated ≥1‐point improvement in FWS and also reported improvement per modified Global Aesthetic Improvement Scale query. The numbers of brown spots and enlarged pores decreased by 45.1% and 28.3%, respectively. Stratification of brown spots data by presence or absence of post‐inflammatory hyperpigmentation revealed paradoxically conflicting data. The improvement detected in wrinkle area and mean wrinkle thickness was less pronounced with overall reductions of 13.4% and 4.8%, respectively. 37 Non‐serious adverse events (AEs) in 22 subjects were reported with most resolving within 14 days or less, and no serious AEs were observed. Conclusions While longer‐term follow‐up is needed, these early study results show that one single‐pass, low energy helium PDR treatment improves facial skin appearance both qualitatively and quantitatively. Studies evaluating higher energy levels and multiple treatment passes are ongoing.